Diagnosis of the dimensions of knowledge management operations in the Kronje company - Ayoub, Abdulsalam Said; Al-Hafdh, Dr. Ali Abdulstaar (The journal of contemporary issues in business and government, 2023)
The study aimed to diagnose knowledge management processes with its dimensions of (knowledge creation, knowledge creation, knowledge storage, knowledge sharing, and knowledge application). Kronji's field of study is for soft drinks, healthy water, juices, dairy and limited energy drinks. The study was based on a sample of 240 respondents from individuals working in the field. The study relied on the descriptive analytical approach, with the use of the questionnaire as the main tool for collecting data related to the field side, as well as conducting personal interviews, as the main and sub-variables were described and correlation and influence relationships and differences between their variables were analyzed, to answer questions related to the study problem and reach objective goals, and in order to process data and information, many statistical methods were used, namely (frequencies, percentages, arithmetic means, standard deviations and factor analysis). Affirmation) by adopting ready-made statistical programs (SPSS. V26) to test the hypotheses of the study and ensure their validity, the study has reached based on the results of statistical analysis to a number of conclusions, the most important of which is the existence of a correlation and a significant impact and at the macro and micro levels of knowledge management processes in the foundations of lean manufacturing.